Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Numbered Head Together Di Kelas III SD - khairun nisa, nadia; Risda Amini (Jurnal Elementaria Edukasia, 2023)
In Class III SDN 01 Sungai Geringging, the Numbered Head Together Type Cooperative Model to Improve Learning Outcomes in Integrated Thematic Learning is the focus of this study. 25 participant including teachers and class III students—were used as research subjects. By combining qualitative and quantitative methods, this study is a classroom action research (CAR). Research findings demonstrate: (1) RPP increased from cycle I's average percentage of 81.25% with a good predicate (B) to cycle II's very good (A) percentage of 97.5%. (2) Cycle I had an implementation rate of 82.81% with a good predicate (B), whereas cycle II had an implementation rate of 93.75% with an excellent predicate (A). The characteristics of the pupils increased from cycle I, where the average percentage was 82.81% with an excellent predicate (B), to cycle II, when the proportion was 93.75% very good (A). (3) Cycle I had an average percentage of 77.82% with an excellent predicate (B), and cycle II had an average percentage of 87.17% with a very good predicate (A) in student learning outcomes. Thus, in class III SDN 01 Sungai Geringging, Padang Pariaman Regency, the cooperative model of the Numbered Head Together type was able to enhance student learning results in integrated thematic learning.